Industrial waste characterization, modification and applications of residues - Anagnostopoulos, Iphigenia; Ayres Negrão, Leonardo Boiadeiro; Bier, Thomas A.; Borg, Gregor; Costa, Marcondes L. da; Ehrenberg, Andreas; Fernandez, Oscar J. C.; Figueira, Bruno A. M.; Galluccio, Sabrina; Gogoi, Champa; Heuss-Assbichler, Soraya; Illikainen, Mirja; et al. (De Gruyter STEM., 2021)
Industrial residues are obtained from all treatments of raw materials in industry during the process of mining, raw materials treatment and final usage. During these processes of enrichment, optimization and utilization of raw materials only part of the original material can be used for the dedicated application and some left-over parts remain. This contribution focuses on residues like mining overburdens, ore residues and ore processing residues like slags, but also on incineration ashes and water purification muds. Natural materials like pozzolanes, due to their potential of CO2-reduction, are also included. Based on this knowledge secondary reusable materials due to their chemical, physical and mineralogical properties can be identified. Also different characterization methods for analysing the potential for further application of these residues are included.